The economic cost of measles: Healthcare, public health and societal costs of the 2012–13 outbreak in Merseyside, UK. Issue 15 (4th April 2016) - Ghebrehewet, Sam; Thorrington, Dominic; Farmer, Siobhan; Kearney, James; Blissett, Deidre; McLeod, Hugh; Keenan, Alex
Abstract: Background: Measles is a highly contagious vaccine-preventable infection that caused large outbreaks in England in 2012 and 2013 in areas which failed to achieve herd protection levels (95%) consistently. We sought to quantify the economic costs associated with the 2012–13 Merseyside measles outbreak, relative to the cost of extending preventative vaccination to secure herd protection. Methods: A costing model based on a critical literature review was developed. A workshop and interviews were held with key stakeholders in the Merseyside outbreak to understand the pathway of a measles case and then quantify healthcare activity and costs for the main NHS providers and public health team incurred during the initial four month period to May 2012. These data were used to model the total costs of the full outbreak to August 2013, comprising those to healthcare providers for patient treatment, public health and societal productivity losses. The modelled total cost of the full outbreak was compared to the cost of extending the preventative vaccination programme to achieve herd protection. Findings: The Merseyside outbreak included 2458 reported cases. The estimated cost of the outbreak was £4.4 m (sensitivity analysis £3.9 m to £5.2 m) comprising 15% (£0.7 m) NHS patient treatment costs, 40% (£1.8 m) public health costs and 44% (£2.0 m) for societal productivity losses. In comparison, over the previous five years in Cheshire and Merseyside a further 11, 793 MMR vaccinations would have been needed to achieve herd protection at an estimated cost of £182, 909 (4% of the total cost of the measles outbreak). Interpretation: Failure to consistently reach MMR uptake levels of 95% across all localities and sectors (achieve herd protection) risks comparatively higher economic costs associated with the containment (including healthcare costs) and implementation of effective public health management of outbreaks. Funding: Commissioned by the Cheshire and Merseyside Public Health England Centre.